Seasonality and range of fruit fly (Diptera Tephritidae) host plants in orchards in Niayes and the Thies Plateau (Senegal) - Ndiaye, O.; Vayssières, Jean-François; Rey, J.; Ndiaye, S.; Diedhiou, P.M.; Ba, C.T.; Diatta, P. (EDP Sciences, 2012)
Introduction. Senegal produces up to 150,000 t of fruit, of which 60,000 t are mangoes. Fruit production is important for the Niayes region, where 60% of total production is of mangoes, with citrus production coming next at 24%. Mango losses have become more substantial since the arrival of Bactrocera invadens in Senegal. The pest population increases in the mango ripening period, but little is known about its secondary hosts. Materials and methods. Fruits of cultivated and wild plants were collected regularly from April to December 2008 inside and around 19 orchards in eleven localities in the Niayes and Thiès areas in Senegal. The samples were monitored to identify any fruit flies present so that a list of host plants could be compiled. For mango, the study focused on establishing the influence of certain parameters such as the variety, the fruit size, the color, the flowering pattern and the physiological levels of infestation due to B. invadens and Ceratitis cosyra. Orchards were classified either as traditional (many mango varieties and many fruit species grown together in a stand) or intensive (fields of monovarietal mango trees), according to their composition and how they were managed. Results and discussion. A total of 663.2 kg of fruit, including those of 24 mango varieties, 13 citrus species with five lime varieties, two orange varieties and four pomelo varieties along with other cultivated and wild plants, were sampled both as fallen fruit and from the trees. Traditional orchards were more infested than the modern ones. B. invadens was significantly dominant over the other flies emerging such as C. cosyra, C. capitata, C. punctata, C. bremii, Bactrocera cucurbitae, Capparimyia bipustulata, Carpomyia sp. and Dacus sp. B. invadens was found on the 24 varieties of Mangifera indica, the 13 citrus species, and the other cultivated plants and wild plants sampled. Some host plants supported a relatively high level of fruit flies before the mango ripening period. Mangifera indica was infested principally by B. invadens and C. cosyra. C. cosyra was significantly present on the first fruit trees to flower, mostly in early varieties, while B. invadens infested all the varieties whatever the fruit development stage, the color, or the flowering pattern. Conclusion.Because of the host plants' diversity and varieties the traditional orchards were more infested than the modern ones. The management of this pest needs an Integrated Pest Management system based on a back-to-basics study of the infesting fruit flies, existing parasitoids and their hosts.